2015
DOI: 10.1007/s10811-015-0618-1
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll catabolites in conditioned media of green microalga Desmodesmus subspicatus

Abstract: Although the appearance of coloured chlorophyll degradation products of higher plants is well known, knowledge about such compounds produced and released particularly by planktonic algae is still limited. Colourless conditioned media (CM) obtained from autotrophic cultures of unicellular green alga Desmosdemus subspicatus turn red after acidification. The accumulation of red pigments in the medium and the growth rate of algae were inversely correlated. The red, crude solution isolated from CM by dialysis and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…2011; Grabski et al . 2016). Further, the evaluation of the effect of cell size on the nitrogen assimilation suggested that large cells show greater ability to store nutrients (Stolte & Riegman 1997; Litchman et al .…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…2011; Grabski et al . 2016). Further, the evaluation of the effect of cell size on the nitrogen assimilation suggested that large cells show greater ability to store nutrients (Stolte & Riegman 1997; Litchman et al .…”
Section: Problem Statementmentioning
confidence: 99%
“…The activity of a plasma membrane cytochrome oxidase generated a H + gradient which serves as a pump to extrude the extra salt out of the cells under high Na + environment. Rai and Gaur (2001) Alkaline Hamm and Smetacek (2007) Size adaptation Phytoplankton As cell size increase, competitive ability decreases for nitrogen and phosphorus Edwards et al (2011) or chlorophyll degradation products released by both Nannochloropsis and Dunaliella (Grabski et al 2016;Misra et al 2016). This observation raises the hypothesis that the exudation might result from the drastic metabolic reorganization occurring in the cell wall in order to adapt to stressful conditions (Jinkerson et al 2011;Grabski et al 2016).…”
Section: Chlamydomonas Eustigmamentioning
confidence: 99%
See 1 more Smart Citation
“…A very close relationship has been always suggested between the chlorophyll catabolic pathway in chlorophytes and in higher plants [26], which is not unlikely assuming the phylogenetic relationship between both taxonomic groups. In fact, open chlorophyll catabolites with similar structures to those of phyllobilins have been identified in Chlorella [26,27] or in Desmodesmus subpicatus [28]. In parallel, chlorophylls are subjected to an oxidative metabolism [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, open chlorophyll catabolites with similar structures to those of phyllobilins have been identified in Chlorella [26,27] or in Desmodesmus subpicatus [28]. In parallel, chlorophylls are subjected to an oxidative metabolism [29,30].…”
Section: Introductionmentioning
confidence: 99%